Regional Innovation System Performance in Indonesia: Case of Semarang and Balikpapan - Kusharsanto, Zulfika Satria; Handayani, Wiwandari; Artiningsih, Artiningsih (The Asian journal of technology management, 2017)
Innovation system which promotes knowledge-based economy, instead of factor driven economy, has been realized by many countries to be an obligatory system to improve national or regional competitiveness. It requires the collaboration of all stakeholders which are related to development to enhance innovation with specialization as the competitiveness value. Semarang and Balikpapan, two emerging cities in Indonesia, has implemented regional innovation system (RIS) with their own strengths and weaknesses. This study uses conceptual analysis with qualitative and quantitative methodology and The Innovation Policy Framework as tool to assess both cities' performance. The study finds that both cities have basic understanding about innovation with specialization such as Semarang develops innovation in city tourism while Balikpapan enhances innovation in green economy. The hard challenges faced by both cities are integration of all stakeholders in enhancing innovation that however is still partially implemented. At the end, this study draws the concept of both cities to develop the system yet without neglecting their existed performance.